Implementasi Kurikulum Multikultural Berbasis Outcome Based Education (OBE) pada Program Studi PGMI UIN Sunan Kalijaga Yogyakarta - Humaira Silfiani; Sukiman Sukiman; Diah Pahmasari Harahap; Armiya Sayidatun Nafi’ah; Isma Nadia Mumtaz (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2025)
This study aims to analyze the implementation of Outcome-Based Education (OBE) and the integration of multicultural values in the curriculum of the Primary Madrasah Teacher Education (PGMI) program at UIN Sunan Kalijaga. Specifically, the study examines the alignment between the formulation of learning outcomes, classroom instructional practices, and assessment strategies, while also identifying challenges in implementing OBE within the context of Islamic higher education institutions (PTKI). A qualitative approach, employing a case study design, was used. Data were collected through in-depth interviews with lecturers and program administrators, classroom observations, and document analysis of the curriculum and OBE-based Semester Learning Plans (RPS). The data were analyzed thematically through stages of data reduction, categorization, and interpretation. The findings indicate that the PGMI curriculum has been developed in accordance with OBE principles, as reflected in the formulation of Program Learning Outcomes (CPL), Course Learning Outcomes (CPMK), and a structured curriculum mapping process. However, the implementation of OBE and the integration of multicultural values in classroom practice remain inconsistent. Variations in instructional methods and assessment approaches suggest that constructive alignment has not yet been fully achieved. This study proposes the concept of semi-alignment to explain the gap between curriculum design and instructional practice. The findings highlight that the successful implementation of OBE in PTKI requires strengthened lecturer capacity, consistent application of authentic assessment, and sustained institutional support through systematic monitoring and mentoring mechanisms.